Nurses' impact on quality of care: lessons from RN4CAST - Walter Sermeus (Nurses and Midwives Association of Slovenia, 2015)
Introduction: The RN4CAST - study (acronym for Nurse Forecasting in Europe) was launched in 2009 and ended in 2011 under the European Union's Seventh Framework Programme. The aim of the RN4CAST-study was to study how features of work environments and qualifications of the nurse workforce impact nurse retention, burnout among nurses and patient outcomes. Methods: The study was conducted in twelve European countries and was conducting a cross-sectional survey in 500 hospitals in which more than 33,000 nurses and more than 11,000 patients were involved. These data were linked to patient outcome data from administrative databases. Results: The study showed that patient outcomes such as patient mortality and patient satisfaction is highly related to nurse staffing characteristics such as patient-to-nurse ratios, nurse qualification and nursing work environment. Also nurse outcomes such as burnout, intention-to-leave, job satisfaction are related to staffing adequacy and nursing work environment. Discussion and conclusion: The RN4CAST study generated a large evidence base of nurse workforce issues across European health systems which is quite unique in terms of the number and qualification of nursing staff, the quality of working environments, burnout rates, job satisfaction rates, intention-to-leave rates that can be used for policy making.